The Missing Link An Introduction to Web Development and Programming - Mendez, Michael; Open Textbook Library (Open Textbook Library, 2014)
Web development is an evolving amalgamation of languages that work in concert to receive, modify, and deliver information between parties using the Internet as a mechanism of delivery. While it is easy to describe conceptually, implementation is accompanied by an overwhelming variety of languages, platforms, templates, frameworks, guidelines, and standards. Navigating a project from concept to completion often requires more than mastery of one or two complementing languages, meaning today's developers need both breadth, and depth, of knowledge to be effective. This text provides the developer with an understanding of the various elements of web development by focusing on the concepts and fundamentals through the examples within, providing a foundation that allows easier transition to other languages and a better understanding of how to approach their work. The reader will be introduced to topics in a manner that follows most project development methods, from initial conceptualization and design through front end development, back end development, and introducing additional concepts like accessibility and security, while focusing on responsive design techniques. Each section of the text includes opportunities to practice the material and assess increased knowledge after examining the topics.
Chapter 1: Brief History of the Internet -- Chapter 2: Current Trends -- Chapter 3: Web Servers -- Chapter 4: Network Basics -- Chapter 5: Website Design -- Chapter 6: Development -- Chapter 7: Markup Languages -- Chapter 8: Creating HTML Files -- Chapter 9: Page Layout -- Chapter 10: Text Layout -- Chapter 11: Navigation -- Chapter 12: Graphics -- Chapter 13: Tables -- Chapter 14: Forms -- Chapter 15: Canvas -- Chapter 16: Media Support -- Chapter 17: Mobile Device Support -- Chapter 18: Tags to Avoid -- Chapter 19: Rule Structure -- Chapter 20: Layout Formatting -- Chapter 21: Font and Text Decoration -- Chapter 22: Responsive Styling -- Chapter 23: Server-Side and Client-Side Scripting -- Chapter 24: Creating PHP Files -- Chapter 25: PHP Errors -- Chapter 26: PHP Output -- Chapter 27: Data Storage -- Chapter 28: Data Manipulation -- Chapter 29: Email -- Chapter 30: File Interaction -- Chapter 31: Structures -- Chapter 32: Functions -- Chapter 33: Objects and Classes -- Chapter 34: JavaScript Syntax -- Chapter 35: JavaScript Examples -- Chapter 36: jQuery -- Chapter 37: Database Types -- Chapter 38: Data Relationships -- Chapter 39: MySQL Data Types -- Chapter 40: Normalization -- Chapter 41: MySQL CRUD Actions -- Chapter 42: Advanced Queries -- Chapter 43: Security -- Chapter 44: Integration Examples -- Chapter 45: Finishing Touches -- Chapter 46: Now What?
In English.
Description based on print resource
Keywords: Computer Science -- Textbooks